Four new species of jumping spiders from Qomolangma National Nature Reserve, Xizang, China (Araneae: Salticidae) - Wang, Cheng; Mi, Xiaoqi; Nyima (Zootaxa, 2025)
Four new species belonging to two genera of jumping spiders from Qomolangma National Nature Reserve, Xizang, China are described: Habrocestoides shuqiangi Wang & Mi, sp. nov. (♂♀), Yaginumaella luoi Wang & Mi, sp. nov. (♂♀), Y. qomolangma Wang & Mi, sp. nov. (♂♀), and Y. zhangae Wang & Mi, sp. nov. (♂♀). Diagnostic photos and a distributional map of the new species are provided.